2016
DOI: 10.1177/1073191115599055
|View full text |Cite|
|
Sign up to set email alerts
|

Assessing Cognitive and Affective Empathy Through the Interpersonal Reactivity Index

Abstract: One aspect of higher order social cognition is empathy, a psychological construct comprising a cognitive (recognizing emotions) and an affective (responding to emotions) component. The complex nature of empathy complicates the accurate measurement of these components. The most widely used measure of empathy is the Interpersonal Reactivity Index (IRI). However, the factor structure of the IRI as it is predominantly used in the psychological literature differs from Davis's original four-factor model in that it a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
91
3
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(104 citation statements)
references
References 46 publications
7
91
3
3
Order By: Relevance
“…The moderate correlation between the IRI empathic concern and personal distress subscales suggests that empathy does not fully embrace emotional availability and responsiveness in perinatal care. The absence of a strong association also resonates with critique on the IRI empathic concern and personal distress subscales' ability to capture emotional aspects (Chrysikou and Thompson, 2016). Results of the current study suggest that although there is conceptual overlap, empathy and emotional aspects of care are not the same.…”
Section: Associations With Empathysupporting
confidence: 63%
“…The moderate correlation between the IRI empathic concern and personal distress subscales suggests that empathy does not fully embrace emotional availability and responsiveness in perinatal care. The absence of a strong association also resonates with critique on the IRI empathic concern and personal distress subscales' ability to capture emotional aspects (Chrysikou and Thompson, 2016). Results of the current study suggest that although there is conceptual overlap, empathy and emotional aspects of care are not the same.…”
Section: Associations With Empathysupporting
confidence: 63%
“…The IRI (Davis, 1980) is a 28‐item self‐report scale measuring individuals’ global concept of empathy across four domains: perspective taking, fantasy, empathic concern, and personal distress. Since its development, the IRI has remained one of the most widely used psychometric tools for measuring the construct of empathy (Chrysikou & Thompson, 2016). The IRI was selected for this study because of its multidimensional design and ability to measure distinct aspects and consequences of empathy.…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, studies involving neurophysiological measures of ACC activation (Bellebaum et al, ; Thoma et al, ) found no significant associations with affective empathy measures. Research has also shown that using combinations or separate subscales of the IRI may not reliably represent cognitive and affective empathy (Chrysikou & Thompson, ). The results of this investigation suggest that future research should consider the use of questionnaires in relation to the measurement of cognitive and affective framework of multidimensional empathy.…”
Section: Discussionmentioning
confidence: 99%
“…For example, some researchers have omitted fantasy and personal distress subscales, as they were suggested to not be valid measures of empathy (Jolliffe & Farrington, 2004;Reniers et al, 2011). Furthermore, others have attributed the inconsistencies in findings due to variations in use and interpretation of the IRI subscales (Chrysikou & Thompson, 2015).…”
mentioning
confidence: 99%